Mothering behind bars: the role of contact maintenance programs on the mothering identity of incarcerated women - Brown, Rebecca R. (Kansas State University, 2016)
The number of women incarcerated within the American penal system has been increasing in recent years. Coinciding with this rise in the incarceration rate for women, there has been increasing concern regarding women parenting behind bars and how incarceration impacts a woman's identity as a mother. As such the purpose of this paper is to examine the connection between participation in contact maintenance programs at the Topeka, Kansas Correctional Facility and their resulting impact on identity work using a sample of 34 incarcerated mothers who participated in this contact maintenance program. Results revealed that through participation in contact maintenance programs incarcerated mothers begin to develop and sustain a more pro- social image of themselves as 'good mothers.' Foundational practices of parenting and the development and sustainment of the mother-child bond are reinforced to facilitate the development of a positive self-image and to lay the groundwork for successful parenting post- release.
Keywords: Contact maintenance program; Identity work; Incarcerated mothers; Incarcerated women; Mother-child bond; Mothering